PENGARUH RETURN ON ASSET,EARNING PER SHARE DAN DEBT TO EQUITY RATIO TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2018 - Neni Lusiana; Kasmadi Kasmadi (Jurnal Riset Manajemen Indonesia, 2019)
This study was conducted with the aim to examine the effect of return on assets, earnings per share and debt to equity ratio on firm value and variables that affect firm value on pharmaceutical sub-sector companies listed on the Indonesia stock exchange in 2016-2018. The population in this study were all pharmaceutical sub-sector companies listed on the Indonesia stock exchange in the 2016-2018 period. The technique used in sampling is purposive sampling method, the samples in this study were selected as many as 10 companies. Hypothesis testing uses multiple linear regression analysis with the help of SPSS 23.00 for windows. The results showed that simultaneous return on assets, earnings per share and debt to equity ratio affect the value of the company. Partially, return on assets and earnings per share affect the value of the company.